Models based on dietary nutrients predicting all-cause and cardiovascular mortality in people with diabetes - Fang Wang; Yukang Mao; Jinyu Sun; Jiaming Yang; Li Xiao; Qingxia Huang; Chenchen Wei; Zhongshan Gou; Kerui Zhang (Scientific Reports)
Abstract Dietary intervention plays a vital role in improving the prognosis of people with diabetes mellitus (DM). Currently, there is a lack of systematic analysis of the relation between dietary nutrients and long-term mortality risk in people with DM. The study aims to establish models predicting long-term mortality and explore dietary nutrients associated with reduced long-term events to guide daily dietary decisions in people with DM. The retrospective cohort study collected 5060 participants with DM from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. The least absolute shrinkage and selection operator (LASSO) regression and random forest (RF) algorithm were applied to identify key mortality-related dietary factors, which were subsequently incorporated into risk prediction nomogram models. The receiver operating characteristic (ROC) curve, calibration plot and decision curve analysis (DCA) were utilized to evaluate the performance of the models. The association of key dietary nutrients with all-cause and cardiovascular mortality were visualized by restricted cubic spline (RCS) models both in the whole and subgroups by sex, age, drinking and smoking status. The overall median age of the cohort was 62.0 years (interquartile range (IQR) 52.0–70.0), 2564 (50.67%) being male. During a median follow-up period of 56.0 months, 997 (19.70%) all-cause deaths were recorded, with 219 (21.97%) of which being ascribed to cardiovascular disease. The nomogram models based on key dietary nutrients identified by LASSO and RF demonstrated a significant predicative value for all-cause and cardiovascular mortality. Dietary fiber and magnesium were the common predictive nutrients in the two nomogram models. The RCS curve revealed that dietary fiber and magnesium were negatively associated with long-term mortality in the whole and subgroups of people with DM after adjustment of potential confounders. The diet of people with DM is closely associated with mortality. The nomogram models based on dietary nutrients can predict long-term mortality of people with DM, and the higher intake of dietary fiber and magnesium was associated with reduced risks of both long-term all-cause and cardiovascular mortality.